Sublingual Misoprostol versus Oxytocin to Induce Labor in Term Premature Rupture of Membranes in Pregnant Women: A Randomized Single-Blind Controlled Trial. (13th February 2022) - Unthanan, Suchada; Petcharat, Kanyarat; Prommas, Sinart; Smanchat, Buppa; Bhamarapravatana, Kornkarn; Suwannarurk, Komsun
Abstract : Objective . The aim of this study was to compare maternal and neonatal outcomes between sublingual misoprostol and oxytocin on stimulating labor in term premature rupture of membranes (PROM) in pregnant women. Materials and method . This randomized single-blind control trial was conducted at Bhumibol Adulyadej Hospital (BAH), Royal Thai Air Force, Bangkok, Thailand, between September 2020 and February 2021. Subjects were term pregnant women who had PROM and came to BAH for delivery. Participants were allocated into study (misoprostol) and control (oxytocin) groups. The study and control groups were, respectively, administered sublingual misoprostol and intravenous oxytocin to induce labor. Induction time and second stage of labor were recorded. Neonatal outcomes and maternal and fetal complications were also recorded and analyzed. Result . A total of 170 women were enrolled and equally divided into study and control groups. Mean maternal age, body mass index, parity, gestational age, and bishop score of both groups were comparable. Induction time of the study group was statistically shorter than the control group (338 and 399 min, respectively). Duration of active phase (450/427 min) and the second stage (19/21 min) of labor between study and control groups were not significantly different. Cesarean section delivery rate of study was lower than the control group (13.3 and 28.8%, p = 0.002 ). Intrapartum complications, neonatal outcomes, and intra- and postpartum complications among both groups were not significantly differentiated. There was no instance of postpartum hemorrhage or uterine rupture in the present study. Conclusion . Induction time and cesarean section rates of sublingual misoprostol group were significantly lower than the intravenous oxytocin group in full-term PROM pregnancy.